Application of Religious Culture In Improving The Quality of Education - Khoirun Nisa; Tsabita Dina Hanifah (SCHOOLAR: Social and Literature Study in Education, 2022)
This research is aimed to examine application of religious culture in increasing quality of education in MTsN 3 Jombang. The kind of research used is qualitative research with descriptive approacement. Data is collected through observation, interview and documentation. The technique of analyzed data is carried out Through phase data reduction, data presentation and summary (conclusion). Result of research that to upgrade quality of education in MTsN 3 Jombang is unlimited only full filling input and output aspect, but more important than that is processes, one of the processes application of religious culture. The realities of religious cultures in MTsN 3 Jombang include: Culture 5S (Senyum, sapa, salam, sopan, santun), Pray Duha, reciting Qur’an, study amtsilati, praying together and istigotsah, takhasus programme, used uniform cover aurat and separating male and female activity. Application of religious culture can influence quality education MTsN 3 Jombang and make positive attitude (morality) for thourghout students.